Face and Address Term in Cross Cultural Classroom Communication - Titik Ceriyani Miswaty; Syamsurrijal Syamsurrijal; M. Zaki Pahrul Hadi; Taufik Suadiyatno (Universitas Cokroaminoto Palopo, 2021)
This article focused on the usage of address term in saving and maintaining face in cross-cultural classroom. In order to gain the result of this research, this research occupied conversation analytic framework to explore classroom interaction. The data used is conversation during classroom interaction. There are 13 kinds of conversation collected in this research. In the data occurrences from Sasaknese and non-Sasaknese students, the non-Sasaknese students using “side” to refer “you” instead of using the word “you” in their native language. Furthermore, the use of the address term has proven to be able to save and protect the face of the interlocutor. although the results of data analysis show that students use address terms more as a way of respecting their teachers than teachers to students. but this does not reduce the politeness of the way the teacher talks to the students.